The brief international cognitive assessment for multiple sclerosis (BICAMS): normative values with gender, age and education corrections in the Italian population - Goretti, Benedetta; Niccolai, Claudia; Hakiki, Bahia; Sturchio, Andrea; Falautano, Monica; Minacapelli, Eleonora; Martinelli, Vittorio; Incerti, Chiara; Nocentini, Ugo; Murgia, Monica; Fenu, Giuseppe; Cocco, Eleonora; et al. (BMC neurology, 2014)
Background BICAMS (Brief International Cognitive Assessment for Multiple Sclerosis) has been recently developed as brief, practical and universal assessment tool for cognitive impairment in MS subjects. It includes the Symbol Digit Modalities Test (SDMT), the California Verbal Learning Test-2 (CVLT2) and the Brief Visuospatial Memory Test-Revised (BVMT-R) . In this study we aimed at gathering regression based normative data for the BICAMS battery in the Italian population. Methods Healthy subjects were consecutively recruited among patient friends and relatives. Corrections for demographics were calculated using multivariable linear regression models. Test-retest reliability was assessed using the Pearson correlation coefficient. Results The BICAMS battery was administered to 273 healthy subjects (180 women, mean age 38.9 ± 13.0 years, mean education 14.9 ± 3.0 years). Test-retest reliability was good for all the tests. Conclusions The study provided normative data of the BICAMS for the Italian population confirming good test-retest reliability which can facilitate the use of the battery in clinical practice, also for longitudinal patient assessments.